213 COLONIC HISTOPLASMOSIS PRESENTING AS PNEUMOPERITONEUM. Issue 1 (1st January 2007) - Sharma, A.; Bhasin, L.; Patel, S.; Panther, R.
Abstract : Objective: To underscore histoplasmosis as a differential diagnosis in patients with acute abdomen. Case: A 55-year-old African American male with no significant past medical history presented with worsening generalized weakness and fatigue for 3 to 4 months, associated with shortness of breath, loss of appetite, and gradual weight loss. The Patient was a lifelong resident of Alabama, married with one heterosexual partner, and a security guard by occupation with a 40-pack-year history of smoking. Physical examination consisted of pallor, loss of facial muscle mass, temporal wasting, and orthostatic hypotension. Complete blood count revealed WBC 3.8, Hb 8.7, Hct 26.7, and MCV 75, and ELISA for HIV was positive. The patient was found to have positive fecal occult blood and underwent colonoscopy, revealing an ulcerative lesion around 90 cm from the anus, with possible mass effect on the colon. He improved clinically following hydration and blood transfusion. While awaiting the results of Western blot, colon biopsy, and lymphocyte panel, the patient was discharged with an outpatient appointment and was lost to follow-up. Four weeks later, the patient presented with severe abdominal pain and was found to have pneumoperitoneum and underwent resection of the colon. Histopathologic examination of the resected colon showed abundant histiocytes and several organisms in clusters compatible with Histoplasma capsulatum . Postoperative course was complicated by sepsis and respiratory failure. Pleural fluid and sputum cultures grew Histoplasma . He was diagnosed with disseminated histoplasmosis involving the pulmonary and gastrointestinal systems. The patient was treated successfully with amphotericin B and was discharged from the hospital on Pneumocystis and Histoplasma prophylaxis. Discussion: Gastrointestinal histoplasmosis (GIH) may be misdiagnosed as inflammatory bowel disease, malignancy, or other intestinal diseases, leading to inappropriate therapies and unnecessary surgical intervention. This case serves to remind physicians to have a high index of suspicion of GIH in patients with immunosuppression, especially in endemic areas, presenting with the above types of gastrointestinal abnormalities. Disseminated histoplasmosis is lethal if untreated, and treatment is highly effective.